Review of the applications of laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) to the analysis of biological samples - Pozebon, Dirce; Scheffler, Guilherme L; Dressler, Valderi L; Nunes, Matheus A. G (Journal of analytical atomic spectrometry, 2014)
Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) has received significant attention over the last 10 years and has been widely used for the analysis of biological samples. The technique allows the determination of elements and isotopes in biological tissues and related materials with a spatial resolution typically ranging from 10 to 100 μm. When compared to other techniques usually employed to obtain bioimages, the greater advantage of LA-ICP-MS is its higher sensitivity. The literature survey over the last 10 years concerning the use of LA-ICP-MS for biological tissue analysis is reviewed in this article. Instrumentation, strategies of calibration for quantitative analysis, challenges and recent advances in this field are discussed. Applications of the isotope ratio (IR), including tracer experiments, and isotope dilution (ID), are reviewed for biological samples (briefly for proteins, in order to show the utility of LA-ICP-MS). Bioimaging methods, studies and applications for animal and plants tissues are emphasized, demonstrating the importance of bioimaging of metals and metalloids in biomedical research, bioaccumulation and bioavailability studies for ecological and toxicological risk assessment in humans, animals and plants. The usefulness of the IR associated with bioimaging for predicting geographical origin, habitat, movement of subjects, diet and lifestyle are also demonstrated. Laser ablation inductively coupled plasma mass spectrometry has been proven to be useful in life sciences as can be observed by the increasing number of publications in this field.